Farm-level barriers to the adoption of precision agriculture technologies in the South African maize industry : variable rate application, section control, and guidance - Blaker, Timothy Nigel (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.